Skeletal Effects of Inducible ERα Deletion in Osteocytes in Adult Mice. (22nd July 2022) - Doolittle, Madison L.; Saul, Dominik; Kaur, Japneet; Rowsey, Jennifer L.; Eckhardt, Brittany; Vos, Stephanie; Grain, Sarah; Kroupova, Kveta; Ruan, Ming; Weivoda, Megan; Oursler, Merry Jo; Farr, Joshua N.; et al.
ABSTRACT: Estrogen is known to regulate bone metabolism in both women and men, but substantial gaps remain in our knowledge of estrogen and estrogen receptor alpha (ERα) regulation of adult bone metabolism. Studies using global ERα‐knockout mice were confounded by high circulating sex‐steroid levels, and osteocyte/osteoblast‐specific ERα deletion may be confounded by ERα effects on growth versus the adult skeleton. Thus, we developed mice expressing the tamoxifen‐inducible CreERT2 in osteocytes using the 8‐kilobase (kb) Dmp1 promoter ( Dmp1 CreERT2 ). These mice were crossed with ERα fl//fl mice to create ERα ΔOcy mice, permitting inducible osteocyte‐specific ERα deletion in adulthood. After intermittent tamoxifen treatment of adult 4‐month‐old mice for 1 month, female, but not male, ERα ΔOcy mice exhibited reduced spine bone volume fraction (BV/TV (−20.1%, p  = 0.004) accompanied by decreased trabecular bone formation rate (−18.9%, p  = 0.0496) and serum P1NP levels (−38.9%, p  = 0.014). Periosteal (+65.6%, p  = 0.004) and endocortical (+64.1%, p  = 0.003) expansion were higher in ERα ΔOcy mice compared to control ( Dmp1 CreERT2 ) mice at the tibial diaphysis, reflecting the known effects of estrogen to inhibit periosteal apposition and promote endocortical formation. Increases in Sost (2.1‐fold, p  = 0.001) messenger RNA (mRNA) levels were observed in trabecular bone at the spine in ERα ΔOcy mice, consistent with previous reports that estrogen deficiency is associated with increased circulating sclerostin as well as bone SOST mRNA levels in humans. Further, the biological consequences of increased Sost expression were reflected in significant overall downregulation in panels of osteoblast and Wnt target genes in osteocyte‐enriched bones from ERα ΔOcy mice. These findings thus establish that osteocytic ERα is critical for estrogen action in female, but not male, adult bone metabolism. Moreover, the reduction in bone formation accompanied by increased Sost, decreased osteoblast, and decreased Wnt target gene expression in ERα ΔOcy mice provides a direct link in vivo between ERα and Wnt signaling. © 2022 American Society for Bone and Mineral Research (ASBMR).